2020
DOI: 10.32505/atfaluna.v3i2.1961
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Komunikasi Interpersonal dan Latar Belakang Pendidikan terhadap Profesionalisme Kepala PAUD

Abstract: The professionalism headmaster of PAUD strongly influences the quality of PAUD institution. The low competence professionalism headmaster of PAUD is the leading cause of the low quality of education, including the headmaster of PAUD with limited insights regarding early childhood education, lack of communication with colleagues has an impact on motivation and morale found in the field. This research is a quantitative study with multiple regression analysis. This study aims to determine the effect of interperso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…Selain itu (Utami & Wahyuni, 2020) menjelaskan bahwa guru profesional bisa dipengaruhi oleh : a) jenjang pendidikan atau kualifikasi pendidikan b) keikut sertaanya dalam berbagai kegiatan pengembangan diri misalnya mengikuti pelatihan, penyetaraan, workshop serta berbagai penataran yang telah diikuti sesuai bidangnya c) mampu membangun hubungan interaksi yang baik dan luas pada semua lapisan masyarakat pada umumnya d) mampu mengembangkan etos kerja atau peningkatan kinerja yang mengutamakan pelayanan prima dan bermutu tinggi dalam bidang pendidikan e) mengadopsi dan mengembangkan dalam memanfaatkan teknologi dan komunikasi. Selain itu, mengutip perjelasan dari (Hadiyanto, 2004) Peran guru sebagai pembimbing ini lebih diutamakan, karena kehadiran guru disekolah tersebut merupakan kehadirannya untuk membimbing peserta didik menjadi manusia cakap, dewasa dan mempunyai sikap yang arif.…”
Section: Hasil Dan Pembahasan Konsep Pengembangan Dalam Keprofesianunclassified
“…Selain itu (Utami & Wahyuni, 2020) menjelaskan bahwa guru profesional bisa dipengaruhi oleh : a) jenjang pendidikan atau kualifikasi pendidikan b) keikut sertaanya dalam berbagai kegiatan pengembangan diri misalnya mengikuti pelatihan, penyetaraan, workshop serta berbagai penataran yang telah diikuti sesuai bidangnya c) mampu membangun hubungan interaksi yang baik dan luas pada semua lapisan masyarakat pada umumnya d) mampu mengembangkan etos kerja atau peningkatan kinerja yang mengutamakan pelayanan prima dan bermutu tinggi dalam bidang pendidikan e) mengadopsi dan mengembangkan dalam memanfaatkan teknologi dan komunikasi. Selain itu, mengutip perjelasan dari (Hadiyanto, 2004) Peran guru sebagai pembimbing ini lebih diutamakan, karena kehadiran guru disekolah tersebut merupakan kehadirannya untuk membimbing peserta didik menjadi manusia cakap, dewasa dan mempunyai sikap yang arif.…”
Section: Hasil Dan Pembahasan Konsep Pengembangan Dalam Keprofesianunclassified
“…It is indicated that a high level of educational background will also lead to a high level of professionalism due to the breadth of knowledge and insight that an individual receives from an educational institution (Utami et al, 2020). Educational background of teachers can affect the professional competence of teachers.…”
Section: Teacher Educational Background and Teaching Experience On Th...mentioning
confidence: 99%
“…The head of the foundation in an Early Childhood Education (PAUD) institution is a leader responsible for and entrusted with the duty as an educational driver. This role involves structurally guiding the school's head, teachers/instructors, students, parents of the students, and various stakeholders or partnerships in the context of achieving the goals related to the activities and the implementation of PAUD learning (Utami, Raihana, & Wahyuni, 2020). Leadership is a composition to influence and provide direction to subordinates in order to achieve specific objectives.…”
Section: Introductionmentioning
confidence: 99%